Using Ear Molding to Treat Congenital Auricular Deformities - Chen, Yu; Wang, Wei; Wang, Yue; Mao, Xiang (Frontiers in Pediatrics, 2021)
Objective: To explore the utility of ear molding in the treatment of congenital auricular deformations. Study design: A retrospective chart/photograph review of a consecutive series of infants treated with the EarWell System from 2017 to 2020 was performed. Data on type of auricular deformity, treatment side, and auricular length and width were collected weekly for all study participants. Result: A total of 173 patients (274 ears) with congenital auricular anomalies were included. The treatment duration for lop ears and Stahl's ears was shorter than for other deformations. The mean treatment EarWell duration of participants who started ear molding within 14 days of birth was shorter than that of those who started treatment more than 14 days after birth with the same ear deformation. For participants with unilateral ear deformities, the length and width of both the affected and healthy ears increased over the course of treatment, equalizing after 3 weeks. For participants with bilateral ear deformities, the length and width of both ears increased rapidly over the first 3 weeks of treatment, and the length and width of both ears gradually equalized after treatment. Conclusion: Ear molding is an important intervention for treating congenital auricular deformations, and can increase auricular length and width. Early identification and initiation of treatment is crucial in the management of congenital auricular deformation.